2003
DOI: 10.1089/089771503767168474
|View full text |Cite
|
Sign up to set email alerts
|

Moderate Hypothermia Improves Neurobehavioral Deficits after an Epidural Focal Mass Lesion in Rodents

Abstract: The objective of this study was to evaluate the effects of a moderate, intraischemic hypothermia on the behavorial deficits up to 4 weeks after induction of a focal mass lesion. A focal epidural mass lesion was induced by an epidural balloon. The severity of the trauma was defined by the balloon volume and flattening of electroencephalography. Hypothermia (32 degrees C) was induced as soon as maximum balloon infIation was reached. Ischemia was extended over 30 min. After reperfusion, normothermic (n = 24) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 74 publications
1
5
0
Order By: Relevance
“…Recently the relation between hypothermia and EEG has been reported by [5] [6]. These results may support the hypothesis that therapeutic hypothermia, which is to lower the body's temperature after cardiac arrest, dramatically increases the chances of recovery and improves the neurological outcome [7]- [9].…”
Section: Introductionsupporting
confidence: 52%
“…Recently the relation between hypothermia and EEG has been reported by [5] [6]. These results may support the hypothesis that therapeutic hypothermia, which is to lower the body's temperature after cardiac arrest, dramatically increases the chances of recovery and improves the neurological outcome [7]- [9].…”
Section: Introductionsupporting
confidence: 52%
“…Recently the relation between hypothermia and EEG has been reported by [7], [8]. These results may support the hypothesis that therapeutic hypothermia, which is to lower the body's temperature after cardiac arrest, dramatically increases the chances of recovery and improves the neurological outcome [9]- [11].…”
Section: Introductionmentioning
confidence: 57%
“…First the DWT coefficients within each window are obtained as (8) Then, to calculate p(m) within each transformed window WC(r; n; w; Δ), intervals in (6) are modified (9) Similar to p n (m) in SE, the probability, within each window WC(r; n; w; Δ) is calculated using (9) instead of (6). Finally IQ is defined as (10) Thus, we can explore the IQ evolution of the whole data {s(i) : i = 1 ⋯ N} with (10).…”
Section: B Measuring Information Quantitymentioning
confidence: 99%
“…133,134 The results of clinical trials of hypothermia as a neuroprotectant in TBI may have been influenced by late induction or by complications. Most preclinical studies suggest significant neuroprotection from hypothermia if induced early (within 2 h), [135][136][137][138][139][140] but in the NABIS:H study, the mean time from injury to the achievement of a target body temperature of 33°C was more than 8 h. 130 The authors suggested later that they may have missed the treatment window. 141 Adverse effects of hypothermia include a higher incidence of cardiac arrhythmias, coagulopathies, pulmonary infections, hypothermia-induced diuresis and electrolyte derangements.…”
Section: Hypothermia For Neuroprotectionmentioning
confidence: 99%